Pengukuran Kinerja UMKM Berdasarkan Key Performance Indicators (KPI) Metode Balanced Scorecard - Priska Shirty Thelma Mawuntu; Reynaldo Christian Aotama (Universitas Warmadewa, 2022)
Small and Medium Enterprises (SMEs) play a crucial role in economic growth, creating employment, and poverty alleviation. However, they often face numbers of obstacles that hinder them to grow which raises the need to undertake good managerial practices such as performance measurement. Measuring performance enables firms SMEs to evaluate their performance and to conduct any corrective actions for improvement in the future. This study aims to measure the performance of Culinary SMEs in the city of Tomohon using key performance indicators based on each perspective of the Balanced Scorecard. There are nine indicators used in this study namely net profit margin, efficiency ratio, customer satisfaction, customer profitability, product innovation, manufacture cycle effectiveness, employee satisfaction, employee productivity, and employee training. The results show a good performance of the SMEs in financial and customer perspectives, however, the internal business and growth and learning perspectives indicate a poor performance specifically in product innovation and employee training indicators. Overall, the performance of the Culinary SMEs in Tomohon is not optimal which requires more improvement both from the SMEs themselves but also from the government as authorities.